Nimodipine dose reductions in the treatment of patients with aneurysmal subarachnoid hemorrhage - Dengler, Nora; Sarrafzadeh-Khorassani, Asita (Neurocritical care, 2016)
Background The incidence of cerebral infarction and poor outcome in patients with aneurysmal subarachnoid hemorrhage (aSAH) is reduced by oral nimodipine but acute effects of the drug may include a significant decrease in mean arterial blood pressure (MAP). A dose reduction or discontinuation of the drug is recommended if recurrent MAP drops occur. The aim of our study was to evaluate the frequency and clinical significance of nimodipine dose modifications in patients suffering from aSAH.Methods270 patients were included in our retrospective analysis of consecutively collected data of patients suffering from aSAH. The local treatment protocol was in accordance to national and international guidelines. Nimodipine was intended to be applied orally with a dosage of 60 mg every 4 h.ResultsOnly 43.6 % of patients eligible for vasospasm prophylaxis with nimodipine received the full daily dose of 60 mg every 4 h. In 28.6 %, the dose had to be reduced by 50 % due to a significant reduction in blood pressure after administration and/or high dose of catecholamines. In 27.7 % of patients, oral administration of the drug was discontinued for the same reason. Dose reduction and discontinuation occurred with a significantly higher frequency in patients in poor clinical condition. Application of the full nimodipine dosage decreased the risk of unfavorable clinical outcome in multivariate analysis (OR 0.895, p = 0.029).ConclusionsOur results show that dose reduction or discontinuation of nimodipine due to changes in MAP occur frequently in clinical routine and may be associated with unfavorable clinical outcome.